Characterization of Extracellular Penicilin G Acylase Produced by A New Local Strain of Bacillus subtilis BAC4 - SUPARTONO SUPARTONO; ENNY RATNANINGSIH; SADIJAH ACHMAD; OEI BAN LIANG (HAYATI Journal of Biosciences, 2008)
Penicillin G acylase (PGA) which catalyses penicillin G hydrolysis reaction is a key enzyme for the industrial production of penicilin G derivatives used in therapeutics. A new local strain of Bacillus subtilis BAC4 was found capable of producing extracellular PGA. However, characteristics of this extracellular PGA are not known. The goal of this research was to characterize the extracellular PGA produced by B. subtilis BAC4. Enzyme production was carried out by batch fermentation, followed by enzyme purification and characterization of the PGA. The PGA activity was determined by the Kornfeld method, with optimal activity for hydrolysing penicillin G observed at 43 oC and pH 8.5. The activation energy of penicillin G hydrolysis by the PGA of B. subtilis BAC4 was determined as 4.9 kcal.mol-1 and Vmax and Km values were found to be 0.7 Ã‚Âµmole.min-1.mg-1 and 3.5 mM respectively. PGA catalytic activity was competitively inhibited by phenylacetic acid with an inhibition constant, Ki(PAA) , of 347.2 mM. It was concluded that the extracellular PGA of B. subtilis BAC4 can hydrolyse penicillin G efficiently. Key words: PGA, extracellular, Bacillus, local